Identification of fingerprint patterns of down syndrome patients in special schools in Padang and students of the Faculty of Dentistry class of 2020, Baiturrahmah University: Identifikasi pola sidik jari penderita down syndrome pada sekolah luar biasa di Padang dan mahasiswa Fakultas Kedokteran Gigi angkatan 2020 Universitas Baiturrahmah - Firdaus; Resti Iswani; Suci Lia Ayu Prameswari (Makassar Dental Journal PDGI Makassar, 2024)
The term Dermatoglyphics or fingerprints are features of the skin on the fingertips that are formed at the embryonic stage and persist without change. Fingerprints are often used for the investigation of disease and behavior of individuals, and have been widely studied in groups with genetic disorders, behavior of individuals, and have been extensively studied in groups with genetic disorders such as Down Syndrome, mental retardation. This study was aimed to determine the identification of fingerprint patterns of patients with DS at special schools or SLB in the city of Padang and students of the Faculty of Dentistry Class of 2020 Baiturrahmah University with 3 types of fingerprint patterns. This quantitative observational analytic study uses descriptive research methods with a cross-sectional design shows that on students Faculty of Dentistry Class of 2020 most fingerprints are ulnar loop type (52.2%) and DS sufferers (92.5%). It is concluded that in the ulnar loop type is higher for Down Syndrome patients compared to the faculty of dentistry students 2020.